Foundations of kinesiology - Oglesby, Carole A.; Henige, Kim; McLaughlin, Douglas W.; Stillwell, Belinda (Jones & Bartlett Learning, 2018)
"Foundations of Kinesiology is intended for undergraduate kinesiology, physical education, and health science students with an interest in fitness, therapeutic exercise, teaching, coaching, and sport management. Introduction to Kinesiology committed to three core approaches: 1) holistic, 2) learner-centered, and 3) skill development"--Provided by publisher.